Estimating the value of medal success at the 2010 Winter Olympic Games - Humphreys, B. R.; Johnson, B. K.; Mason, D. S.; Whitehead, J. C. (Working Paper No. 2011-20, 2011)
We estimate Canadians` willingness to pay (WTP) for success by Team Canada in the 2010 Winter Olympic Games. The Canadian government subsidized elite athletes in the run up to the 2010 Games through the Own the Podium program, which was designed to increase Canada`s medal count. WTP estimates from a contingent valuation method study using data from nationally representative surveys before and after the Vancouver Games suggest that Own the Podium generated intangible benefits equal to 2 to 4 times its cost. The aggregate value of the intangible benefits generated by the program was between $251 million and $3.4 billion.